Genome-Wide Identification, Characterisation and Phylogenetic Analysis of 52 Striped Catfish (Pangasianodon hypophthalmus) ATP-Binding Cassette (ABC) Transporter Genes - Leonard Whye Kit Lim; Hung Hui Chung; Han Ming Gan (Tropical Life Sciences Research, 2022)
The Pangasianodon hypophthalmus (striped or tra catfish) is a Pangasiidae family member famous for its high unsaturated fatty acid content flesh. This riverine catfish can breathe in the air unlike the channel catfish. One of the most well-known ecotoxicological protein superfamily, the ATP-binding cassette (ABC) transporters, has been characterised in channel catfish through a genome-wide approach. Therefore, it is interesting to unearth these proteins within the striped catfish genome for a comprehensive comparison across all catfishes available. A total of 52 ABC transporters were discovered from the striped catfish genome. The motif analysis has unconcealed various unshared characteristics of some catfishes. The phylogenetic analysis has evidenced its effectiveness in the successful annotations of these transporter proteins. Duplicated genes such as ABCA1, ABCB3, ABCB6, ABCC5, ABCD3, ABCE1, ABCF2 as well as ABCG2 were uncovered within the striped and channel catfish genomes. This entire set of ABC transporters yields precious genomic data for future ecotoxicological, biochemical and physiological research in striped catfish.